Identifying patients at high risk for poor outcome after intra arterial therapy for acute ischemic stroke - Hallevi, Hen (2009)
BACKGROUND: Intra-arterial recanalization therapy (IAT) is increasingly utilized for acute stroke. Despite high rates of recanalization the outcome is variable. We attempted to identify predictors of outcome that will enable better patient selection for IAT. METHODS: All patients who underwent IAT at the UT Houston Stroke Center were reviewed. Poor outcome was defined as modified Rankin Scale score 4–6 on hospital discharge. Findings were validated in an independent dataset of 175 patients from UCLA Stroke Center RESULTS: 190 patients were identified. Mean age 62, median baseline NIHSS .18. Recanalization rate 75%, symptomatic hemorrhage rate 6%, and poor outcome rate 66%. Variables associated with poor outcome were: age, baseline NIHSS, admission glucose, diabetes, heart disease, previous stroke and the absence of mismatch on the pre-treatment MRI. Logistic regression identified three variables independently associated with poor outcome: age (p=0.049, OR=1.028), NIHSS (p=0.013, OR=1.084), admission glucose (p=0.031, OR=1.011). Using this data, we devised the Houston IAT (HIAT) score: 1 point for age>75; 1 for NIHSS>18 and 1 point for glucose>150mg/dL (range 0 to 3). The percentage of poor outcome by HIAT score was: score of 0: 44%; 1: 67%; 2: 97%; 3: 100%. Recanalization rates were similar across the scores (p=0.4). Applying HIAT to the external cohort showed comparable trends in outcome and nearly identical rates in the HIAT 3 tier. CONCLUSIONS: The HIAT score estimates the chances of poor outcome after IAT even with recanalization. It may be useful in comparing cohorts of patients and when assessing the results of clinical trials.